Золушка из банды: [повести] / Сергей Рокотов - Рокотов Сергей Григорьевич (Вне закона, 2001)
Экземпляры: ф.22 (2003) / Инвентарный номер: 47415 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 66 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44